2001
DOI: 10.1034/j.1399-3046.2001.00024.x
|View full text |Cite
|
Sign up to set email alerts
|

Extravesical ureteroneocystostomy with and without internalized ureteric stents in pediatric renal transplantation

Abstract: The use of ureteric double-J stents and the Lich-Gregoir (extravesical) technique of ureteroneocystotomy have both been shown to decrease the rate of urologic complications in adult kidney transplantation (Tx). There are, however, few studies of the systematic use of stents in pediatric renal Tx. Between 1991 and 1997, 32 consecutive pediatric renal transplant recipients routinely received a 6F-12 cm indwelling double-J stent and were studied prospectively. These patients were compared with 32 consecutive pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 9 publications
2
37
2
1
Order By: Relevance
“…The overall rate of incidences of urological complications in our study was 7.5%, comparable with other major centers [4][5][6][7] . Vascular integrity of the donor ureter, the anastomotic technique employed and avoidance of technical mishaps such as kinks and twisting of the ureter are major factors impacting the success of ureterovesical anastomosis [8] . Most transplant centers prefer U-C as the initial approach for ureteral reimplantation for kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall rate of incidences of urological complications in our study was 7.5%, comparable with other major centers [4][5][6][7] . Vascular integrity of the donor ureter, the anastomotic technique employed and avoidance of technical mishaps such as kinks and twisting of the ureter are major factors impacting the success of ureterovesical anastomosis [8] . Most transplant centers prefer U-C as the initial approach for ureteral reimplantation for kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…However, other surgeons have reported that routine ureteral stenting is unnecessary for patients with a low risk of urological complications [6] . It must be kept in mind that refinement of surgical techniques and the introduction of new immunosuppressive protocols have also decreased the incidence of urological complications [8] .…”
Section: Discussionmentioning
confidence: 99%
“…(19) French ve ark. pediatrik transplantasyon hastalarında 32 stent kullanılarak yapılan nakillerle, stentsiz 32 hastanın sonuçlarını karşılaştırmıştır (20). Stent kullanılan 2 hastada idrar kaçağı gözlenirken, stent yerleştirilmeden yapılan nakillerde sadece 1 hastada obstrüksüyon saptanmıştır.…”
Section: Discussionunclassified
“…Although the extra-vesical technique of ureteroneocystostomy is believed to reduce the rate of urological complications in both adult and paediatric patients [21,22,23,24], the use of ureteric stenting devices remains controversial. Some units do not routinely use stent placement at transplantation [14].…”
Section: Introductionmentioning
confidence: 99%